2006
DOI: 10.1002/cne.21165
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala interconnections with the cingulate motor cortex in the rhesus monkey

Abstract: Amygdala interconnections with the cingulate motor cortices were investigated in the rhesus monkey. Using multiple tracing approaches, we found a robust projection from the lateral basal nucleus of the amygdala to Layers II, IIIa, and V of the rostral cingulate motor cortex (M3). A smaller source of amygdala input arose from the accessory basal, cortical, and lateral nuclei, which targeted only the rostral region of M3. We also found a light projection from the lateral basal nucleus to the same layers of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 201 publications
(292 reference statements)
9
120
1
Order By: Relevance
“…This may, however, just reflect these small size of the areas, their proximity to the corpus callosum, and the care taken to avoid including callosal tissue in the cingulate mask. In addition, although an area with a high amygdala connection probability was identified that resembled the core amygdala-connecting region in macaque, there was no strong evidence for interconnection between dorsal cingulate motor regions and amygdala in the present study, although such connections exist, albeit at a lower density, in the macaque (Morecraft et al, 2007). It should, however, be noted that the region identified as interconnected with amygdala in the present study resembles that found to vary in tandem with amygdala in morphometric analyses of the human brain (Pezawas et al, 2005).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This may, however, just reflect these small size of the areas, their proximity to the corpus callosum, and the care taken to avoid including callosal tissue in the cingulate mask. In addition, although an area with a high amygdala connection probability was identified that resembled the core amygdala-connecting region in macaque, there was no strong evidence for interconnection between dorsal cingulate motor regions and amygdala in the present study, although such connections exist, albeit at a lower density, in the macaque (Morecraft et al, 2007). It should, however, be noted that the region identified as interconnected with amygdala in the present study resembles that found to vary in tandem with amygdala in morphometric analyses of the human brain (Pezawas et al, 2005).…”
Section: Discussioncontrasting
confidence: 88%
“…The probability of connections between cingulate and amygdala was assessed because, in the monkey, the amygdala is interconnected with anterior cingulate cortex (Porrino et al, 1981;Amaral and Price, 1984;Carmichael and Price, 1995;Ghashghaei et al, 2007;Morecraft et al, 2007).…”
Section: Definition Of Target Masksmentioning
confidence: 99%
“…The shared involvement of OFC and ACC S in reinforcementguided decision making is consistent with the areas' shared anatomical connections with brain structures critical for reinforcement learning such as the amygdala and ventral striatum (Porrino et al, 1981;Morecraft et al, 2007). The differences in OFC and ACC S function are also, however, consistent with differences in their relative strength of connection with sensory and motor systems.…”
Section: Discussionsupporting
confidence: 68%
“…Alternatively, the late pMCC response may reflect an integrative response to inputs reaching the pMCC through multisynaptic corticocortical connections from both sensory and associative areas. Indeed, the pMCC receives inputs from multiple cortical sources, including other subregions of CC, posterior parietal cortex, insula, amygdala, and motor and premotor cortices, and sends back projections to most of them (Baleydier and Mauguière, 1980;Morecraft and Van Hoesen, 1992Hatanaka et al, 2003;Morecraft et al, 2007).…”
Section: Anatomical Pathways Supporting the Pain Cingulate Responsesmentioning
confidence: 99%